Hubungan Kekerabatan Kupu- Kupu (Lepidoptera) Berdasarkan Karakter Morfologi di Desa Pombewe, Sulawesi Tengah - Artha, Fandy; Dhafir, Fatmah; Ashari, Abdul; Trianto, Manap; Bustamin, Bustamin; Rafiqa, Rafiqa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the kinship of butterflies (Lepidoptera) based on morphological characters in Pombewe Village, Central Sulawesi. The research method used was the roaming method with free collection technique. Morphological characters observed included antenna shape, wing color and pattern, and body size. Kinship analysis was conducted using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) with the help of Paleontological Statistics software (PAST 4.03). The results identified 13 butterfly species from the Nymphalidae family, namely Euploea redtenbacheri, Euploea algea, Euploea hewitsonii, Danaus genutia leucoglene, Cyrestis strigata, Danaus genutia genutia, Euploea eunice, Vindula erota, Doleschallia polibete, Acraea terpsicore, Ideopsis juventa, Parantica cleona, and Cyrestis paulinus. The relationship dendrogram showed two main clusters with four relationship categories, namely very close relationship (Cyrestis strigata and Cyrestis paulinus, IS = 100%), close relationship (Euploea hewitsonii and Danaus genutia leucoglene, IS = 74.07%), not close relationship (Cyrestis strigata and Euploea eunice, IS = 32.25%).